Edukasi, Pelatihan Teknologi Pengolahan, dan Pengembangan Produk Olahan Purun di Desa Mekar Jaya, Kecamatan Wampu, Kabupaten Langkat: Education, Processing Technology Training, and Purun Product Development in Mekar Jaya Village, Wampu District, Langkat Regency - Batubara, Ridwanti; Affandi, Oding; Hakim, Luthfi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Mekar Jaya Village is one of the villages in Wampu District, Langkat Regency, with high purun potential and many purun artisans in the community. However, until now the purun processed by the community is only mat products. The purpose of the training activities carried out is to educate and train the community about processing technology and purun product development. The activity method is in the form of discussions about educating the management and processing of purun processed products and training in making purun crafts guided by purun artisans trainers. The activity results showed that the community's knowledge about purun management and how to use it increased. After the training, especially in dyeing technology, increased the public's knowledge about purun coloring and encouraged the community to innovate in terms of coloring and processed purun-based products.